Determination of chitin content in shells of selected crab species available in Jaffna - Thapeetha, Y.; Digamadulla, K.M.D.S.; Sashikesh, G.; Sivashanthini, K. (University of Jaffna, 2020)
—In the post-war context, Jaffna crab industry is developed, exporting live, fresh de-shelled and processed crabs all around the world. Human consumes only 40% of the crab’s weight as meat and the rest is thrown into the environment as waste shell. This unutilized waste crab shell contains large amount of chitin which can be extracted and utilized for different applications in cosmetics, agriculture, food, medicine and waste water treatment. The present study was carried out to find out the chitin content in selected, most abundant crabs such as Portunus pelagicus, Thalamita crenata and Portunus sanguinolentus available in Jaffna peninsula, during the period of July - October, 2017. Crabs were deshelled and the shells were dried, ground and screened through < 0.5 mm sieve. Fine particles of the crab shells samples were deproteinized by treating with 3.5% (w/v) NaOH solution and demineralized by treating with 1 N HCl. The extracted chitin was confirmed via the functional group using Fourier Transmission Infrared Spectroscopy. Higher yield percentage of extracted chitin was observed in the shells of Portunus sanguinolentus (23.38±1.11%) than Portunus pelagicus (15.39±0.73%) and Thalamita crenata (15.84±1.30%). The study revealed that the percentage of protein and calcium carbonate in Portunus sanguinolentus are 18.94± 1.74% and 62.29±1.92%, in Portunus pelagicus are 22.91±2.03% and 61.70±1.97% and in Thalamita crenata are 15.24±1.45% and 68.92±1.70%, respectively
Keywords: Chitin; Crab shell; Demineralization; Deproteinization